Blockade of NKG2D/NKG2D ligand interaction attenuated cardiac remodelling after myocardial infarction. Issue 4 (11th October 2018) - Matsumoto, Kotaro; Obana, Masanori; Kobayashi, Arisa; Kihara, Miho; Shioi, Go; Miyagawa, Shigeru; Maeda, Makiko; Sakata, Yasushi; Nakayama, Hiroyuki; Sawa, Yoshiki; Fujio, Yasushi
Abstract: Aims: Accumulating evidence demonstrates that cardiomyocyte death contributes to the onset and progression of heart failure (HF) after myocardial injury. Recent studies revealed that immune/inflammatory reactions play important roles in cardiovascular diseases. However, it remains unclear whether immunosurveillance system, which eliminates cytopathic cells, including infected or malignant cancer cells, is involved in cardiomyocyte death, though cardiomyocytes are exposed to pathological stresses during post-infarct remodelling. The aim of this study is to clarify the pathophysiological significance of Natural Killer Group 2 member D (NKG2D)/NKG2D ligand (NKG2DL)-mediated cell death in HF after myocardial infarction (MI). Methods and results: MI was generated by ligating left anterior descending artery in mice. The expression of NKG2D, NKG2DLs, especially Retinoic acid early induced transcript-1ɛ (Rae-1ɛ), perforin and granzyme B was concomitantly up-regulated after MI. Immunohistological analysis revealed that Rae-1 was expressed on the membranes of injured cardiomyocytes in the infarct and border area. The MI-induced increase of Rae-1 expression was suppressed in p53 −/− mice and Rae-1 was induced by the overexpression of p53. We identified p53-binding sites in Rae-1ɛ gene promoter, by chromatin immunoprecipitation assay, indicating that Rae-1 expression was mediated partially through p53. Flow cytometric analysis indicated that NKG2D-expressing immune cells in the post-infarct myocardium were mainly γδT cells. The co-culture with γδT cells increased the frequency of apoptotic cells in the cultured cardiomyocytes. The blockade of NKG2D/NKG2DL interaction by intraperitoneal injection of anti-Rae-1ɛ antibody after MI reduced the frequency of apoptotic cardiomyocytes, accompanied by suppression of cardiac fibrosis, attenuating cardiac dysfunction. Finally, tamoxifen-inducible cardiomyocyte-specific Rae-1ɛ overexpressing mice exhibited the susceptibility to post-infarct remodelling with increased cardiomyocyte apoptosis and severer cardiac dysfunction. Conclusion: The interaction between immune cells and cardiomyocytes via NKG2D/NKG2DL induces cardiomyocyte death, exacerbating cardiac remodelling after MI. The blockade of NKG2D/NKG2DL interaction could be a promising therapeutic strategy against HF.